Funciones como asistente en el área de tesorería de la empresa cia. minera Poderosa S.A. - Diestra Nolasco, Evita Andrea (2018)
The development of mining in the country is a risky activity since it involves large investments in terms of exploration, with uncertain results, although over time these companies continue to improve mechanisms to reduce such uncertainty. In any case, the investment is necessary to develop the sector depending on some key variables, such as mining potential and policy factors. The economic growth of companies requires management to implement internal control procedures, which ensure an orderly and efficient management of the business, as well as detecting and / or preventing fraud and error that affect business results through the implementation of policies, processes and procedures (controls) adopted to safeguard business assets, as well as the timely preparation of reliable financial information. The present job of professional proficiency was developed in the treasury area of the company Cia. Minera Poderosa S.A., with the purpose of obtaining the title of Public Accountant. It is concluded that the decisions taken in the treasury area totally and irrevocably affect the income statement of the company Cía. Minera Poderosa S.A., so it is an area that contributes directly to the value of the company. It is recommended that the company Cia. Minera Poderosa S.A .must have a liquidity management, in order to guarantee the necessary funds at the right time and in the appropriate currency, in order to comply with the obligations contracted, thus having a correct administration of working capital.